1985
DOI: 10.1007/bf01849310
|View full text |Cite
|
Sign up to set email alerts
|

Orally administered ketoconazole rapidly appears in seminal plasma and suppresses sperm motility

Abstract: Ketoconazole has been shown to exert spermatostatic effects in vitro on ejaculated dog, monkey, and human spermatozoa. Oral administration of the compound to adult male beagle dogs (50-246 mg/kg) or rhesus monkeys (85-100 mg/kg) was associated with a decline in motility of sperm in ejaculates obtained after dosing. In dogs the decline in sperm motility was correlated with the presence of ketoconazole in the seminal plasma, although the measured concentrations of ketoconazole were no more than one tenth that ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Little is known so far about the effect of ketoconazole on dog semen. Vickery, Burns, Zaneveld, Goodpasture, and Bergström (1985) showed that administration of ketoconazole was associated with a decline in motility of sperm. We showed for first time that prolonged treatment with ketoconazole led to azoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known so far about the effect of ketoconazole on dog semen. Vickery, Burns, Zaneveld, Goodpasture, and Bergström (1985) showed that administration of ketoconazole was associated with a decline in motility of sperm. We showed for first time that prolonged treatment with ketoconazole led to azoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…Ketoconazole is an inhibitor of cellular division and has been shown to exert spermatostatic effects in several species including the dog, rabbit, monkey and man (Kutzler and Wood, 2006).Its oral administration to adult male dogs @ 50-246 mg/kg was associated with a decline in motility of sperm in ejaculates within 4 hours of dosing (Vickery et al, 1985b). However, Heckman et al(1992) in their study with mice and rats observed lack of correlation between steroid levels and sperm immobilization, along with rapid in vivo and in vitro effects on sperm motility and they concluded that ketoconazole is probably not a viable approach to the development of a male contraceptive.…”
Section: Ketoconazolementioning
confidence: 99%
“…For example, ketoconazole (11), alpha-chlorohydrin (12) and emblein (13) have been tested in animals. However, the suppression of spermatogenesis was incomplete and systemic toxicity was limiting (14).…”
Section: Introductionmentioning
confidence: 99%